DEVELOPMENT OF FLIPBOOK BASED SMART CARD LEARNING MEDIA IN SCIENCE LEARNING TO IMPROVE STUDENT LEARNING MOTIVATION CLASS III SD - Parinduri, Wina Mariana; Lubis, Renni Ramadhani; Rambe, Titin Rahmayanti; Rambe, Nurhamimah (Universitas Negeri Medan, 2022)
This research is research Research and Development (R&D). This study uses the Four D development model. In this study it was only carried out at the development stage. This research was conducted in class II at SD IT Hamas Stabat. The research was carried out in the even semester of the 2021/2022 school year. The subjects in this study were 20 grade II students at SDIT Hamas, 11 male students and 9 female students. The object in this study is flipbook based smart card learning media. Data collection techniques in this study were observation, interviews, tests, questionnaires and documentation. The stages in the four D development model are define, design, develop, disseminate. The results of the validation test by experts, namely media experts, were 89.00%, while the results of the material validation test were 88.06%. The results of material validation and media validation are categorized as very feasible. The results of student learning motivation on flipbook-based smart card learning media amounted to 79.07%.